Gender equity and land: The role of corporate social responsibility in Niger Delta, Nigeria - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2022)
We examine the impact of multinationals oil companies' (MOCs) corporate social responsibility (CSR) on enhancing land rights for rural women. A total of 1,200 women were sampled across the Niger Delta region of Nigeria. Results from the use of a combined propensity score matching and logit model show that MOCs' CSR using global memorandum of understanding (GMoU) model recorded significant success in various policy mechanisms to improve gender equality in land access. The linkages include joint-titling modalities, land leasing, land use certificate issuances, community and territorial land delimitation interventions for both agricultural production and security in Nigeria's oil host communities.
Keywords: 330; Gender equity; corporate social responsibility; multinational oil companies; land; sub-Saharan Africa